2024
DOI: 10.3389/fpain.2024.1288024
|View full text |Cite
|
Sign up to set email alerts
|

Pain and the biochemistry of fibromyalgia: patterns of peripheral cytokines and chemokines contribute to the differentiation between fibromyalgia and controls and are associated with pain, fat infiltration and content

Björn Gerdle,
Olof Dahlqvist Leinhard,
Eva Lund
et al.

Abstract: ObjectivesThis explorative study analyses interrelationships between peripheral compounds in saliva, plasma, and muscles together with body composition variables in healthy subjects and in fibromyalgia patients (FM). There is a need to better understand the extent cytokines and chemokines are associated with body composition and which cytokines and chemokines differentiate FM from healthy controls.MethodsHere, 32 female FM patients and 30 age-matched female healthy controls underwent a clinical examination tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 154 publications
0
1
0
Order By: Relevance
“…Thus, these findings help to address critical knowledge gaps regarding fat and lean body mass contributions to the development and persistence of chronic MSK pain, especially among older adults. BMI cannot explain differences in muscle fat infiltration, intramuscular compounds (metabolites) and production of proinflammatory cytokines and chemokines that each may facilitate pain ( 20 ). In the current study, we found that greater lean mass was associated with less widespread pain, supporting the protective role of lean tissue mass in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these findings help to address critical knowledge gaps regarding fat and lean body mass contributions to the development and persistence of chronic MSK pain, especially among older adults. BMI cannot explain differences in muscle fat infiltration, intramuscular compounds (metabolites) and production of proinflammatory cytokines and chemokines that each may facilitate pain ( 20 ). In the current study, we found that greater lean mass was associated with less widespread pain, supporting the protective role of lean tissue mass in older adults.…”
Section: Discussionmentioning
confidence: 99%